Simultaneous saccharification and fermentation of sago hampas into biobutanol by Clostridium acetobutylicum ATCC 824 - Husin, Hazwani (2018)
The increasing prices of the petrol have driven the researchers towards the utilisation of various renewable resources for biofuel production. Renewable resources such as sago hampas composed of 86.3% potential sugars from starch and lignocellulosic materials with only 3.3% of lignin. High carbohydrate contents, low percentage of lignin content and no pretreatment process is required, make the sago hampas as a promising feedstock for biofuel production including biobutanol. Biobutanol can be produced through acetone-butanolethanol (ABE) fermentation by Clostridium species. Conventional separate hydrolysis and fermentation (SHF) provides desired amount of sugars but requires multiple processing steps and long processing duration. Therefore, simultaneous saccharification and fermentation (SSF) approach was carried out in biobutanol production. SSF process combines saccharification and fermentation in a single vessel, thus reduces steps, costs and time in biobutanol production. Improvement in SSF process was done due to ‘solid effect’ when high substrate concentration was used with the aim of giving better biobutanol productions. This research highlights on potential to convert our country’s underutilised sago hampas into sustainable biobutanol. The optimisation of the saccharification to produce high fermentable sugars yield that affects SSF of biobutanol production was conducted. Enzymatic saccharification of sago hampas was performed by three different approaches, which were the saccharification of sago hampas using 71.4 U/gsubstrate of Dextrozyme glucoamylase, 20 FPU/gsubstrate of Acremonium cellulase and mixture of both. Results showed that, mixture of Dextrozyme glucoamylase and Acremonium cellulase gave the highest reducing sugars concentration with 67.0 g/L. Saccharification of sago hampas was conducted at the conditions needed for acetone-butanol-ethanol (ABE) fermentation (37°C, 150 rpm, anaerobic condition) produced up to 63.2 g/L of reducing sugars. The normal SSF process by Clostridium acetobutylicum ATCC 824 produced 6.75 g/L of ABE with biobutanol concentration of 3.81 g/L and yield of 0.11 g/gsugar. Then, sequential saccharification and simultaneous fermentation (SSSF) was conducted to reduce the solid load in SSF. However, the biobutanol concentration and productivity produced were low about 0.83 g/L and 0.00 g/L.h. In order to improve the biobutanol concentration and productivity, delayed simultaneous saccharification and fermentation (DSSF) was introduced. DSSF has better efficiency since the enzymes and microbe were operated at their optimal conditions. This fermentation generated a biobutanol concentration of 4.62 g/L and 0.5-fold higher biobutanol productivity than normal SSF. In this study, it suggested that the DSSF has the potential to be implemented for the production of biobutanol from sago hampas.